2016
DOI: 10.1016/j.ijheatfluidflow.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

On wall pressure fluctuations and their coupling with vortex dynamics in a separated–reattached turbulent flow over a blunt flat plate

Abstract: DARU-On wall pressure fluctuations and their coupling with vortex dynamicsin a separate d-reattache d turbulent flow over a blunt flat plate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 52 publications
3
18
0
Order By: Relevance
“…Then, transition to turbulence takes place very quickly. Indeed, the largescale spanwise rolls develop into hairpin-like vortices further downstream (Sasaki & Kiya 1991;Hourigan et al 2001;Tenaud et al 2016). As shown by Lasheras & Choi (1988), this three-dimensional pattern is at the basis of the observed presence of streamwise velocity streaks which result from the interaction of counter-rotating pairs of streamwise vortices with the mean shear in analogy with plane free shear layers.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Then, transition to turbulence takes place very quickly. Indeed, the largescale spanwise rolls develop into hairpin-like vortices further downstream (Sasaki & Kiya 1991;Hourigan et al 2001;Tenaud et al 2016). As shown by Lasheras & Choi (1988), this three-dimensional pattern is at the basis of the observed presence of streamwise velocity streaks which result from the interaction of counter-rotating pairs of streamwise vortices with the mean shear in analogy with plane free shear layers.…”
Section: Introductionmentioning
confidence: 89%
“…Subsequently, transition to turbulence sets in very rapidly for x > 0.5 (Winant & Browand 1974;Spalart & Strelets 2000). Under the effect of the mean shear, still strong at these streamwise locations, perturbations of the flow field lead to the lift up and stretching of the primary spanwise vortices thus forming hairpin-like structures (Hourigan et al 2001;Langari & Yang 2013;Tenaud et al 2016) arranged in a staggered manner (Soria et al 1993;Sasaki & Kiya 1991), see the enlargement of figure 3(a). By moving downstream, these hairpin-like structures are stretched and, as shown in figure 4 where the pattern taken by the streamwise vorticity, ω x = ∂w/∂y − ∂v/∂z is reported, the flow motion develops streamwise vortices (Kiya & Sasaki 1985;Bernal & Roshko 1986), which are known to induce entrainment and high-and low-speed streaks (Jiménez 1983).…”
Section: Instantaneous Flow Topologymentioning
confidence: 97%
“…Following Eaton & Johnston (1982), they proposed that the origin of the lowfrequency unsteadiness may be the change of the spanwise coherence of the vortices and the variation in their ability in entraining momentum. Some high-fidelity simulations of similar configurations also show the presence of the low-frequency process whose cause was not elucidated (Tafti & Vanka 1991;Tenaud et al 2016).…”
Section: Unsteadiness Of Separating Flowsmentioning
confidence: 99%
“…In most of these applications, the incoming boundary layer is turbulent and separates either because of an adverse pressure gradient (APG) or a geometric discontinuity (e.g., backward facing step). The separated flow typically exhibits unsteadiness across a broad range of time-scales (Eaton & Johnston (1982); Cherry et al (1984); Kiya & Sasaki (1985); Tenaud et al (2016); Najjar & Balachandar (1998), among others). These unsteady modes can dominate the dynamics of the separation bubble and they have significant implications for the performance of the flow device/system at hand.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of Proper Orthogonal Decomposition (POD) to analyze the extensive data using advanced diagnostics has provided valuable insights. POD analysis of Podvin et al (2014) and Tenaud et al (2016) showed that although the flow exhibited 2 characteristic frequencies corresponding to the flapping and shedding modes, the most energetic motions corresponded to the shedding of large-scale vortices. A quasi-invariance in the spanwise direction was also noted.…”
Section: Introductionmentioning
confidence: 99%